Method for determining the content of hyaluronic acid in hydrogel

By adopting the sonication step in the hydrogel and combining the carbazole reaction method, the problem of determining the crosslinked hyaluronic acid content in the hydrogel in the prior art is solved, and the measurement results of high reliability and repeatability are achieved.

CN114829929BActive Publication Date: 2025-03-07UB CARE SRL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080085773.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-02
Filing Date
2020-11-30
Publication Date
2025-03-07
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and reliably determine the content of crosslinked hyaluronic acid in hydrogels, especially in dermal fillers, where there are interference problems and variability in the result.

Method used

The hydrogel was dissolved by sonication and combined with the carbazole reaction method, the absorbance was measured at a specific wavelength by the reaction of sodium tetraborate and carbazole, and the percentage content of HA was calculated using a standard curve.

Benefits of technology

Reliable and highly repeatable measurement of HA content in hydrogels is achieved, standard deviation is reduced, and interference problems and result variability are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114829929B_ABST
    Figure CN114829929B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for determining the content of hyaluronic acid in a hydrogel, the method comprising the following steps: a) preparing a sulfuric acid solution of sodium tetraborate as reagent A; b) preparing reagent B by dissolving carbazole in ethanol; c) preparing a test solution by dissolving a hydrogel in an aqueous solution; d) treating the test solution with ultrasound for a period of time sufficient to obtain a macroscopically uniform solution; e) preparing a reference stock solution by dissolving glucuronic acid or a substance containing glucuronic acid in an aqueous solution; f) preparing at least three reference solutions by diluting the reference stock solution in an aqueous solution, with a concentration of 0.0005% w / v to 0.0100% w / v; g) preparing a test tube by mixing the reagent A, the reagent B and one of the following: a reference solution, a test solution, a blank aqueous solution and an optional interference solution; placing each test tube on a water bath for at least 5 minutes and then cooling them to room temperature; h) reading the absorbance at a wavelength of 500nm to 580nm relative to the blank and the optional interference solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for determining the hyaluronic acid content in a hydrogel. In particular, the present invention relates to a hydrogel used as a filler and containing hyaluronic acid and cross-linked hyaluronic acid. Background Art

[0002] Hyaluronic acid, also known as hyaluronan or hyaluronate (HA), is considered an important glycosaminoglycan due to its diverse physiological functions. The polymer consists of disaccharide repeats of glucuronic acid (UDP-GlcUA) and N-acetylglucosamine (UDP-GlcNAc) linked by β1→3 and β1→4 glycosidic bonds (Purcell BP, Kim IL, Chuo V, Guinen T, Dorsey SM, Burdick JA, (Incorporation of sulfated hyaluronic acid macromers into degradable hydrogel scaffolds for sustained molecular delivery, Biomaterials Science 2009; 27: 417-281, Volpi N, Schiller J, Stern R, Soltes L, Roles, metabolism, chemical modifications and applications of hyaluronic acid, Modern Medicinal Chemistry 2009; 16: 1718-452).

[0003] Compared with other glycosaminoglycans, HA is the only non-sulfated polymer that allows the molecule to be rigid and linear. It is produced in the plasma membrane of all mammalian cells, amphibians and bacteria by an integral membrane enzyme called hyaluronan synthase (HAS) (Chen WYJ, Abatangelo G, the role of hyaluronan in wound repair, Wound Repair and Regeneration 1999; 7: 79-893), which has several isotypes according to its production organism. In humans, HA is present in all organs, and is especially abundant in connective tissue (Fraser JR, Laurent TC, the turnover and metabolism of hyaluronan, Ciba Foundation Seminar 1989; 143 (41-49): 281-5). HA reaches higher concentrations in the vitreous humor (Brewton RG, Mayne R, Mammalian vitreous humor contains a molecular network of hyaluronan: electron microscopic analysis of the hyaluronan binding region (G1) of aggrecan and connexin, Exp. Cell Res. 1992; 198: 237-49), in the synovial fluid of joints (Engstrom-Laurent A, Hyaluronan in joint diseases, J. Int. Med. 1997; 242: 57-606) and in cartilage tissue of the umbilical cord (Yanagishita M, Proteoglycans and hyaluronan in the female reproductive organs, EXS. 1994; 70: 179-90), and is responsible for maintaining tissue homeostasis (Fraser JR, Laurent TC, Laurent UB, Properties, distribution, function and turnover of hyaluronan, J. Int. Med. 1997; 242: 27-33).

[0004] It is reported that with aging, HA production decreases, which leads to dehydration and loss of elasticity of the skin, resulting in the appearance of wrinkles (Gold M, The science and art of hyaluronic acid dermal fillers in cosmetic applications, J Cosm Dermatol 2009;8:301-7). HA is characterized by several chemical properties that make it attractive for different applications: high hygroscopicity, its viscoelastic properties, high biocompatibility, non-immunogenicity and the absence of toxic products upon degradation. The use of HA has been explored in ophthalmic cosmetics (De Figueiredo ES, de Macedo AC, de Figueiredo PFR, de Figueiredo RS, Applications of hyaluronic acid in ophthalmology Arq Bras Oftalmol. 2010;73:92-5), surgery (Kogan G, Soltes L, Stern R, Gemeiner P, Hyaluronic acid: a natural biopolymer with a wide range of biomedical and industrial applications, Biotechnology Express 2007;29:17-25), as a drug delivery system (Brown MB, Jones SA, Hyaluronic acid: a unique topical carrier for topical delivery of drugs to the skin, Journal of the European Academy of Dermatology and Venereology 2005;19:308-18), rheumatology (Greenberg DD, Stoker A, Kane S, Cockrell M, Cook J JL, Biochemical effects of two different hyaluronic acid products in a co-culture model of osteoarthritis, Osteoarthritis and Cartilage 2006; 14: 814-22), otolaryngology (Ramos HVL, Neves LR, Martins JRM, Nader HB, Pontes P, Effects of aging on hyaluronic acid concentrations in the vocal cords of female rats, 2012; 78: 14-8) and urology (Schiraldi C, Gatta A La, Rosa M De: Biotechnological preparation of hyaluronic acid and its application in biopolymers, 2010; 387-412). However, of all the previously mentioned applications, HA is more frequently used in the field of dermatology in dermal fillers. Finally, in tissue engineering, HA is used as a mechanically and physically adequate support for tissues that can be implanted into living organisms without causing allergic or immune responses (Nesti LJ, Li WJ, Shanti RM, Jiang YJ, Jackson W, Freedman BA, Kuklo TR, Giuliani JR, Tuan RS, Intervertebral disc tissue engineering using a novel hyaluronic acid-nanofiber scaffold (HANFS) amalgam. Tissue Eng Part A 2008;14:1527-37).

[0005] The popularity of dermal fillers has grown rapidly in recent years because they provide restorative and enhanced aesthetic improvements previously achievable only through surgery, but at a lower cost and with limited to no recovery time. According to data from the American Society of Aesthetic Plastic Surgery (ASAPS), more than 1.6 million dermal filler treatments were performed in 2011, making it the second most popular non-surgical cosmetic procedure performed in the United States after neuromodulators; the latter procedure is often performed in conjunction with dermal filler injections (American Society of Aesthetic Plastic Surgery, National Database of Cosmetic Surgery Statistics 2012, available from http: / / www.surgery.org / sites / default / files / ASAPS-2011-Stats.pdf., accessed on September 13, 2013). As public awareness and acceptance of dermal fillers grows, the market size is also growing. Their main indications are the filling of wrinkles and folds and the correction of soft tissue loss due to disease or age (Rzany B, Hilton S, Prager W et al., Expert guide to the use of porcine collagen in aesthetic medicine, J Dtsch Dermatol Ges. 2010;8(3):210-217). Fillers are increasingly used in volume replacement and enhancement procedures (Goldberg DJ, Legal consequences of off-label filler use, Dermatologic Treatment 2006;19(3):189-193), including cheek and chin augmentation, tear trough correction, rhinoplasty, midface volumizing, lip augmentation, hand rejuvenation and correction of facial asymmetry.

[0006] Intermediate-duration biodegradable fillers, such as non-crosslinked collagen and hyaluronic acid (HA) fillers, are reabsorbed fairly quickly by the body, so their effects are relatively short-lived. HA derivatives are the most widely used biodegradable fillers in Europe and the United States (Zielke H, Wolber L., Wiest L, Rzany B, Risk profile of different injectable fillers: results of the Injectable Filler Safety Study (IFS Study), Dermatologic Surgery 2008;34(3):326-335) and generally have effects lasting 6-18 months, depending on the source and extent of crosslinking and the concentration and particle size of each product. HA is a linear polymerized dimer of N-acetylglucosamine and glucuronic acid that differs in the proprietary method used to crosslink its dimers, the extent and method of crosslinking its chains, the uniformity and size of its particles, and its concentration (Funt D, Pavicic T, Dermal fillers in aesthetics: an overview of adverse events and treatment approaches, Clinical, Cosmetic and Investigative Dermatology 2013:6 295-316).

[0007] Cross-linking procedures are widely performed to improve the mechanical properties of HA and extend the duration of HA in vivo. A common method is to form hydrogels by covalently cross-linking HA polymer chains into a three-dimensional network with different cross-linking agents (Agerup, B., Berg, P., & Akermark, C, (2005) Non-animal stable hyaluronic acid: a new formulation for the treatment of osteoarthritis, Biopharmaceuticals (2005) 19 (1), 23-30; Edsman, K., Hjelm, R., Larkner, H., Nord, LI, Karlsson, A., Wiebensjo, A et al., Intra-articular duration after a single injection of DurolaneTM into the rabbit knee, Cartilage (2011) 2 (4), 384-388), the most common of which are 1,4-butanediol diglycidyl ether (BDDE), divinyl sulfone (DVS), polyethylene glycol diglycidyl ether (PEGDE). HA hydrogels formed by cross-linking have become important for many medical and aesthetic applications. The mechanical and physical properties of hydrogels depend on the degree of modification and cross-linking (La Gatta, A., Schiraldi, C., Papa, A., & De Rosa, M, (2011) Comparative analysis of commercial dermal fillers based on cross-linked hyaluronic acid: physical characterization and in vitro enzymatic degradation, Polymer Degradation and Stability (2011) 96(4), 630-636; Stocks, D., Sundaram, H., Michaels, J., Durrani, MJ, Wortzman, MS, & Nelson, DB (2011) Rheological evaluation of the physical properties of hyaluronic acid dermal fillers, Journal of Dermatological Pharmacy, 10(9), 974-980). Having methods and definitions for determining the cross-linking parameters is very important in establishing the relationship between the degree of modification and cross-linking and the mechanical properties as well as the biocompatibility.

[0008] Dermal fillers are classified as Class III medical devices. Therefore, they must display the appropriate CE marking on their sterile packaging, including a four-digit number reflecting the Notified Body. In addition, these products must also contain an accompanying leaflet or a link to a digital leaflet. In addition to the product directives, healthcare professionals residing in the United States must limit their use of these products to a list of injectable fillers that have been approved by the Food and Drug Administration (FDA). Unfortunately, no such list exists in the EU, however, efforts are underway to generate one. This shortcoming makes it difficult to know exactly what is legal on the market. However, similar to medications, illegal HA-containing products can be purchased online and intercepted by customs or during routine inspections of different shipping companies. Therefore, there is an increasing need for quality inspectors to analyze the percentage of HA in suspected HA-containing dermal fillers.

[0009] The current quantitative method for HA content is based on the method described in the European Pharmacopoeia for determining the amount of HA present in the raw material (Ph. Eur European Pharmacopoeia, Council of Europe, Strasbourg, France, 8th edition, 2016). In this colorimetric method, carbazole interacts with the uronic acid obtained after acid hydrolysis of HA and produces a violet color that absorbs at 530 nm. This determination is considered to be not very specific and is not suitable for hydrogels. Therefore, alternative methods have been developed for the identification and quantification of linear native HA in hydrogels. These methods include HPLC-based methods using photodiode array detectors (PDA), light scattering, fluorescence or mass spectrometry (MS) detectors (SB Frazier, KARoodhouse, DE Hourcade and L. Zhang, Open Glycoscience, 2008, 1, 31-39; N. Volpi, F. Galeotti, B. Yang and RJ Linhardt, Handbook of Natural Experiments, 2014, 9, 541-558). In addition, methods based on enzyme-linked immunosorbent assay (ELISA) and turbidimetric methods have been developed (S. Haserodt, M. Aytekin and R. A. D. Weik, Glycobiology, 2011, 21, 175-183; N. Oueslati, P. Leblanc, C. Harscoat-Schiavo, E. Rondags, S. Meunier, R. Kapel and I. Marc, Carbohydrate Polymers, 2014, 4, 102-108). However, only turbidimetric and carbazole methods have been reported to be compatible with the quantification of cross-linked HA, which is usually the preferred form in which this molecule is present in dermal fillers. The first method, similar to the carbazole assay, also suffers from possible interference from other GAGs. Therefore, it is crucial for public health authorities to develop reliable, effective, low-cost and easy-to-apply strategies for the identification and quantification of cross-linked HA for routine analysis of dermal fillers suspected of containing HA.

[0010] Recently, a specific and selective HA identification and quantification method has been proposed, in which an additional extraction step before the carbazole microassay was able to solve possible interference problems that could be encountered when dealing with suspected illegal samples (Vanhee C., Desmedt B., Baudewyns S., Kamugisha A., Vanhamme ME Bothy., JL, Kovackova S., Courselle P., Deconinck E, Characterization of dermal fillers suspected of containing hyaluronic acid, Analytical Methods, 2017, 9, 4175). However, this method is rather lengthy and still presents a wide variability of results depending on the type of hydrogel used and the type of cross-linked HA.

[0011] There remains a need for a reliable method for quantifying HA in hydrogels that is able to measure the HA content of hydrogels in a reliable manner. Summary of the invention

[0012] The present invention relates to a method for determining the HA content in a hydrogel, the method comprising a sonication step. The sonication step dissolves the hydrogel and allows a more reliable determination of the HA content. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The R values ​​and standard curve equations for the examples are reported. DETAILED DESCRIPTION

[0014] The present invention relates to a method for determining the HA content in a hydrogel, the method utilizing a sonication step. Surprisingly, it has been found that by sonicating a cross-linked hydrogel containing HA, the HA content of the hydrogel can be determined in a reproducible manner and with a low standard deviation.

[0015] The most commonly used method for determining HA in aqueous solutions is defined in the European Pharmacopoeia 5.0, pages 2434-7, which is incorporated herein by reference. Another method for determining glucuronic acid by reaction with carbazole is disclosed by T. Bitter and HM Muir (An Improved Uronic Acid Carbazole Reaction, Analytical Biochemistry, 4, 330-334 (1962)), which is incorporated herein by reference. The present invention is an important improvement over the European Pharmacopoeia method and the method of Bitter et al. applied to hydrogels.

[0016] In a preferred embodiment of the present invention, the method comprises the following steps:

[0017] a. Prepare a sulfuric acid solution of sodium tetraborate as reagent A;

[0018] b. preparing reagent B by dissolving carbazole R in ethanol;

[0019] c. Prepare at least two test solutions by dissolving the substance to be tested in aqueous solution.

[0020] c2. Optionally, the test solution is heated to a temperature above room temperature, preferably 75°C to 85°C, for at least 15 minutes, preferably at least 2 hours, more preferably about 3 hours, preferably while continuously stirring;

[0021] d. treating the test solution with ultrasound for a period of time sufficient to obtain a macroscopically uniform solution;

[0022] e. A reference stock solution is prepared by dissolving glucuronic acid or a substance containing glucuronic acid in an aqueous solution; preferably, the concentration of glucuronic acid or a substance containing glucuronic acid is 0.05wt% to 0.15wt%;

[0023] f. preparing at least three reference solutions by diluting the reference stock solution in an aqueous solution, preferably at a concentration of 0.0005% w / v to 0.0100% w / v, preferably 0.0010% w / v to 0.0050% w / v;

[0024] g. Prepare test tubes by mixing the reagent A, the reagent B and one of the following: a reference solution, a test solution, an aqueous solution (blank) and an optional interfering solution (crosslinker sample or additive sample); place each test tube on a water bath for at least 5 minutes and then cool them to room temperature; preferably, the water bath is a boiling water bath and the duration is about 15 minutes;

[0025] h. Read the absorbance at a wavelength of 500 nm to 580 nm, preferably at a wavelength of about 530 nm, relative to the blank and optionally the interfering sample.

[0026] The percentage content of hyaluronic acid is calculated by interpolating the experimental absorbance values ​​with a reference standard curve obtained starting from known concentrations of substrate. Calculation details:

[0027] - Subtract the average absorbance value of each sample from the average absorbance value of the blank sample;

[0028] - Subtract the average absorbance value of each sample from the average of the crosslinker samples (if available);

[0029] - Calculate the percentage content of hyaluronic acid in the weighed samples by interpolating the experimental absorbance values ​​of each replicate with the reference standard curve.

[0030] There are two possibilities regarding the interference of crosslinking agents and additives. If information about the composition of the hydrogel (including the type of crosslinking agent), its amount and the presence of other additives is available, a solution (interference solution) containing additives and crosslinking agents can be prepared, and the amount of the additives and crosslinking agents is the amount in which they are present in the hydrogel. In all other cases, the exact composition of the hydrogel cannot be known. Therefore, it is impossible to take into account the interference of crosslinking agents and additives. The percentage value of hyaluronic acid obtained at the end of the analysis will probably be higher than the effective amount of HA in the sample in some way.

[0031] The percentage content of sodium hyaluronate in the final product was calculated based on the ratio of (NaHA% x 100) / g of hydrogel. The percentage value of each replicate was subject to an acceptance limit of ±20%. The modal value, mean and standard deviation were calculated.

[0032] Step c2 introduces a step of heating the sample containing the test solution at 75-85° C. for 3 hours. This step is not essential and can be removed; however, it is preferred because it helps to improve the efficiency of the subsequent sonication step.

[0033] Step d (ultrasonication of the sample) represents the most important contribution to the prior art methods. In fact, it has been noted that after the ultrasonication, the sample is much more homogeneous than before, and this reflects a higher analytical reproducibility. Although step c2 is useful, it is not necessary to achieve the destruction of the hydrogel. However, if step c2 is not used, it is necessary to apply more severe ultrasonication conditions to dissolve the hydrogel.

[0034] In a preferred embodiment, the ultrasonic treatment step is carried out using a power of 0.5 W / kg to 50 W / kg, more preferably at a specific power of 0.1 W / kg to 10 W / kg. With regard to the specific energy used during ultrasonic treatment, it is 500 J / kg to 30 kJ / kg, preferably 2 kJ / kg to 20 kJ / kg.

[0035] These parameters are also affected by step c2. When step c2 is performed, a relatively low power or relatively low energy ultrasonic treatment can be used. Therefore, when the method includes step c2, a preferred energy range is between 1 kJ / kg and 10 kJ / kg. When step c2 is not performed, a preferred energy range is between 3 kJ / kg and 30 kJ / kg.

[0036] Another important factor that affects the power and duration of the treatment is the chemical nature of the cross-linked hydrogel. Typically, for each new gel, several trials must be performed to determine the experimental conditions that produce good dissolution of the gel.

[0037] Steps a and b are preferably carried out according to the European Pharmacopoeia, ie for reagent A, 0.95 g of disodium tetraborate are dissolved in 100.0 ml of sulfuric acid and for reagent B, 0.125 g of carbazole are dissolved in 100.0 ml of ethanol.

[0038] In step e, the reference stock solution is prepared by dissolving 50.00 mg to 150.00 mg of glucuronic acid or a substance containing glucuronic acid in 100.00 g of water. As the substance containing glucuronic acid, hyaluronic acid is particularly preferably used.

[0039] Experimental Section

[0040] Analysis of hydrogels

[0041] Prepare Reagent A by dissolving 0.95 g of sodium tetraborate in 100.00 ml of sulfuric acid.

[0042] Prepare reagent B by dissolving 0.125 g of carbazole in 100.00 ml of ethanol.

[0043] Three separate samples of the hydrogel were prepared by dissolving an amount of approximately 0.170 g in water and bringing the total weight to 100 g with additional water. Reported hydrogel weights: S1: 0.1723 g; S2: 0.1808 g; S3: 0.1728 g.

[0044] The hydrogel dispersion was heated at 85° C. for 3 hours. It was then sonicated using a sonicator Q500 (Qsonica LLC) at an amplification of 30%, corresponding to 0.22 W. After sonication, the hydrogel was dispersed in water.

[0045] The reference solution stock was prepared by dissolving 50 mg HA in 100 g water. From this solution, 5 solutions were prepared at the following concentrations (wt%): 0.001, 0.002, 0.003, 0.004, 0.005. In Table 1, the absorbance data obtained from the standard curve read at 530 nm are reported. The mean and standard deviation of the replicates for each point of the standard curve were calculated.

[0046] Percentage of standard Average absorbance Standard Deviation 0 0.049 0.0009 0.001 0.062 0.004 0.002 0.070 0.001 0.003 0.079 0.002 0.004 0.088 0.002 0.005 0.098 0.002

[0047] Table 1

[0048] The mean value obtained for each point of the standard curve was subtracted from the mean value obtained for the blank (0.000% of the substance containing glucuronic acid) (Table 2). Figure 1 Calculate the R value and the equation of the standard curve.

[0049] Percentage of standard Absorbance 0 0 0.001 0.013 0.002 0.022 0.003 0.030 0.004 0.039 0.005 0.049

[0050] Table 2

[0051] Add 5.0 ml of freshly prepared Reagent A to each test tube, pre-cooled to 4°C. Carefully layer each sample on top of the Reagent A in the test tube as follows: Blank: 1.0 mL of water R; Reference solution: 1.0 mL of each diluted reference stock solution; Sample: 1.0 mL of each test solution. Gently shake the tube to dissolve the two phases created by the sample. Add 0.20 mL of Reagent B to each test tube. Recap the tubes, shake, and place them again in the water bath for exactly 15 minutes. Cool them to room temperature. Perform two absorbance analyses for each sample, with eight replicates each time.

[0052] The average absorbance values ​​of the samples were calculated (Table 3).

[0053] sample S1 S1 S2 S2 S3 S3 0.100 0.099 0.088 0.080 0.081 0.095 0.098 0.099 0.084 0.080 0.079 0.095 0.097 0.099 0.085 0.082 0.080 0.094 0.100 0.099 0.085 0.082 0.082 0.095 0.100 0.096 0.087 0.083 0.084 0.093 0.100 0.097 0.087 0.083 0.079 0.093 0.098 0.098 0.091 0.082 0.079 0.095 0.097 0.098 0.087 0.083 0.084 0.094 Average absorbance value 0.0988 0.0981 0.0868 0.0819 0.0810 0.0943

[0054] Table 3

[0055] For each absorbance value obtained for a sample, the mean absorbance value of the blank sample was subtracted (Table 4).

[0056] sample S1 S1 S2 S2 S3 S3 0.0513 0.0503 0.0393 0.0313 0.0323 0.0463 0.0493 0.0503 0.0353 0.0313 0.0303 0.0463 0.0483 0.0503 0.0363 0.0333 0.0313 0.0453 0.0513 0.0503 0.0363 0.0333 0.0333 0.0463 0.0513 0.0473 0.0383 0.0343 0.0353 0.0443 0.0513 0.0483 0.0383 0.0343 0.0303 0.0443 0.0493 0.0493 0.0423 0.0333 0.0303 0.0463 0.0483 0.0493 0.0383 0.0343 0.0353 0.0453

[0057] Table 4

[0058] The equation calculated from the standard curve obtained by each absorbance value of the sample relates to the percentage value of NaHA present in the weighed hydrogel and diluted in 100 g of water, as reported in point C of the method. For example 0.0513 / 9.9705=0.00514%.

[0059] For each absorbance value of the sample (Table 5), the percentage of NaHA present in the final product was calculated with the following ratio: A:100 = B:x; x = B·100 / A

[0060] in:

[0061] A = weight of hydrogel used to prepare the sample;

[0062] B = percentage value of NaHA present in the weighed hydrogel and diluted in water.

[0063] For the first sample S calculated as B = 0.00514, we have x = 0.00514 x 100 / 0.1723 = 2.98326.

[0064] sample S1 S1 S2 S2 S3 S3 2,98326 2,92505 2,17733 1,73354 1,87184 2,68442 2,86684 2,92505 1,95544 1,73354 1,75576 2,68442 2,80863 2,92505 2,01091 1,84449 1,81379 2,62638 2,98326 2,92505 2,01091 1,84449 1,92988 2,68442 2,98326 2,75042 2,12186 1,89996 2,04597 2,56834 2,98326 2,80863 2,12186 1,89996 1,75576 2,56834 2,86684 2,86684 2,34375 1,84449 1,75576 2,68442 2,80863 2,86684 2,12186 1,89996 2,04597 2,62638 average value(%) 2,91050 2,87412 2,10799 1,83756 1,87184 2,64089 Standard Deviation 0,08084 0,06554 0,12135 0,06914 0,12410 0,05145

[0065] Table 5

[0066] The modal values ​​were obtained and the acceptance limits (±20%) for the modal values ​​were calculated.

[0067] *Values ​​exceed the acceptance limit of ±20%.

[0068] Modal value: 2.87%.

[0069]

[0070] Table 6

[0071] The mean % and standard deviation of NaHA were calculated among the values ​​collected within the acceptance interval. For example: mean = 2.76%; standard deviation: 0.16%.

Claims

1. A method for determining the content of hyaluronic acid in a hydrogel, the method comprising the following steps: a. Prepare a sulfuric acid solution of sodium tetraborate as reagent A; b. Prepare reagent B by dissolving carbazole in ethanol; c. preparing a test solution by dissolving the hydrogel in an aqueous solution; d. treating the test solution with ultrasound for a period of time sufficient to obtain a macroscopically uniform solution; e. preparing a reference stock solution by dissolving glucuronic acid or a substance containing glucuronic acid in an aqueous solution; f. preparing at least three reference solutions by diluting the reference stock solution in an aqueous solution at a concentration of 0.0005% w / v to 0.0100% w / v; g. preparing test tubes by mixing the reagent A, the reagent B and one of the following: a reference solution, a test solution, a blank aqueous solution and an optional interfering solution, the interfering solution comprising an additive and a cross-linking agent in an amount that is the amount in which they are present in the hydrogel; placing each test tube in a water bath for at least 5 minutes and then cooling them to room temperature; h. Read the absorbance at wavelengths of 500 nm to 580 nm relative to a blank aqueous solution and an optional interference solution.

2. The method according to claim 1, further comprising the following steps after step c: c2. Heat the test solution to a temperature above room temperature for at least 15 minutes.

3. The method according to any one of claims 1 to 2, wherein: In step g, the water bath is a hot bath.

4. The method according to any one of claims 1 to 3, wherein: In the step d, the ultrasonic treatment is performed at a specific power of 0.5 W / kg to 50 W / kg.

5. The method according to any one of claims 1 to 4, wherein: The ultrasonic treatment was performed at a specific energy of 500 J / kg to 30 kJ / kg.

6. The method according to any one of claims 1 to 5, wherein: The reagent A was a 0.95% w / v solution of disodium tetraborate in sulfuric acid, and the reagent B was a 0.125% w / v solution of carbazole in ethanol.

7. The method according to any one of claims 1 to 6, wherein: In the step c, at least two test solutions are prepared.

8. The method according to any one of claims 1 to 7, wherein: The step g is performed as follows: Add 5 parts of reagent A to each test tube; layer each sample on the reagent A in the test tube as follows: blank: 1 part aqueous solution; reference solution: 1 part reference stock solution for each dilution; Sample: 1 aliquot of each test solution; shake the tube to dissolve the two phases created by the sample; Place each sample in a water bath for at least 5 minutes, then cool them to room temperature; add 0.2 parts of Reagent B to each tube, shake the tubes to dissolve the two phases, and place each tube in a warm water bath for at least 5 minutes.

9. The method according to any one of claims 1 to 8, wherein: After step h, the percentage content of hyaluronic acid is calculated by interpolating the experimental absorbance value with the reference standard curve.

Citation Information

Patent Citations

  • Extraction and purification method of hyaluronic acid with large molecular weight

    CN105254779A

  • Method for detecting content of free sodium hyaluronate in medical cross-linking sodium hyaluronate gel

    CN106053369A